Determining predominating histologic component in malignant mixed mü llerian tumors: is it worth it?. Issue 4 (1st July 2008) - Ozguroglu, M.; Bilici, A.; Ilvan, S.; Turna, H.; Atalay, B.; Mandel, N.; ŞAhinler, İ.
Abstract : Malignant mixed mü llerian tumors (MMMT) are highly aggressive tumors, usually diagnosed in advanced stage. Cases of MMMT derive from either ovary or uterus. In our study, we investigated the role of carcinomatous and sarcomatous component on response to chemotherapy and disease outcome. We retrospectively analyzed 25 patients with MMMT who were treated in our outpatient clinic from 1998 to 2003. All the paraffin specimens were reevaluated according to the histopathologic features (primary site and percentages of carcinomatous and sarcomatous component) and the effect of predominant histologic type on response to treatment. Primary tumor sites were ovary and endometrium in 36% and 64% of patients, respectively. Ten of 25 patients (40%) were treated with a combination chemotherapy regimen of cisplatin–ifosfamide (PI) and 7 patients (28%) were treated with paclitaxel–carboplatin (PC) protocol. Despite chemotherapy, 17.6% of patients had progressive disease. The remaining 13 patients (54.2%) responded to chemotherapy. Response rates of patients treated with PC (100%) were remarkably higher than the response rates of patients treated with PI (66.6%). Moreover, patients with predominating carcinomatous component had a higher response rate (87.5%) than patients with predominating sarcomatous component (66.6%). MMMT are highly chemoresponsive tumors, irrespective of primary site. One of the best predictors to response is the histologic pattern. Predominating histopathologic feature (carcinoma or sarcoma) should be taken into consideration in predicting the response and planning the chemotherapy regimen.